Quality Control Analysis to Reduce Defects in Drawn Textured Yarn Products Using the Six Sigma Method (DMAIC) - Ade Irpansah; Muhammad Ihsan; Indra Gumelar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
PT XYZ is a company engaged in the production of Drawn Textured Yarn (DTY) that continued to experience a high level of product defects, particularly the Dyeing Reject defect type, which accounted for 91.712% of total defects during the January-December 2025 period. This condition indicated that the production process was not yet statistically stable and operated at a low sigma capability level of 2.68 sigma. This study aimed to identify the root causes of defects and to formulate improvement proposals to reduce the number of defective products in the DTY production process using the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. In the Measure stage, process stability was assessed using a P-Control Chart, along with DPMO and sigma-level calculations. In the Analyze stage, root causes were identified using a Pareto Diagram, a Fishbone Diagram, and Failure Mode and Effect Analysis (FMEA). The results showed that the root causes originated from machine, man, material, and method factors, with a total Risk Priority Number (RPN) of 2,155. In the Improve stage, improvement proposals were developed using 5W+1H analysis, which reduced the total RPN to 454, a decrease of 1,701 points (78.9%). The Control stage focused on process standardization, continuous monitoring, and operator training to sustain the improvements achieved and to drive the production process toward a zero-defect target.